(Sorption Isotherm Model for Dendeng) - Rizal Alamsyah; Putiati Mahdar; Rotua Eva Irene (Warta Industri Hasil Pertanian, 1996)
A study was The study was aimed at designing adsorption and desorption model of "dendeng" by investigating its static equlibrium moisture content conducted at 30 degree C and 40 degree C,relative humidity (RH)level 32,43,62,63.5,75,80,and 81% for adsorption model,and11,32,43,62,63.5,755 for desorption model.Six model of courie bradley,halsey,oswin,and clen-clayton were employed and modified to investigate a model which appropriate for "dendeng"composition.Before gaining the models and cerves it were initally calculated some constants.The modification of cauries model gave the best results for both adsorption and desorption condition.